Association between Combined Structure Function Index and Glaucoma Severity - Shumpei Ogawa; Yoshimasa Tanabe; Yoshinori Itoh; Takahiko Noro; Hisato Gunji; Tadashi Nakano (Journal of Ophthalmology)
The aim of this study was to investigate the relationship between combined structure function index (CSFI) and standard automated perimetry (SAP) parameters such as mean deviation (MD) and visual field index (VFI) in open-angle glaucoma (OAG). We retrospectively reviewed medical records from September 2009 to July 2015, which included 195 eyes of 195 patients with OAG or normal-tension glaucoma who underwent SAP and optical coherence tomography on the same day (male: female, 128 : 67; mean age, 61.4 ± 11.3 years; mean spherical equivalent, −2.39 ± 2.3 D). We divided participants into three stages based on MD value: early, MD > −6 dB; middle, −6 dB ≥ MD ≥ −12 dB; and advanced, MD < 12 dB. We then evaluated correlations between CSFI and SAP parameters in each stage using Pearson’s correlation coefficient. Mean CSFI (%), mean MD (dB), and VFI (%) in each stage were early (22.4, −2.13, and 94.0); middle (47.9, −8.78, and 75.4); and advanced (68.3, −17.32, and 49.0), respectively. Correlations between CSFI and whole, early, middle, and advanced MD were −0.88 (p<0.001), −0.68, −0.24, and −0.76, respectively. Correlations between CSFI and whole, early, middle, and advanced VFI were −0.86 (p<0.001), −0.59, −0.20, and −0.83, respectively. Consistency between CSFI and SAP indices in middle-stage glaucoma was low.